2017
DOI: 10.1080/00223344.2017.1379124
|View full text |Cite
|
Sign up to set email alerts
|

Histories of Leprosy: Subjectivities, Community and Pacific Worlds

Abstract: Leprosy (or Hansen's disease) was a problem in the colonial Pacific. To control the disease, administrations there and elsewhere tried to isolate so-called 'lepers'. After a cure became available from the 1940s, this policy of segregation gave way; and by 2000 the World Health Organization's goal of 'eliminating' leprosy as a global health burden was declared met. Yet leprosy remains a challenge in many parts of the Pacific and the world. In the Pacific, the historiography of leprosy also raises questions. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…El DLQI se compone de 10 preguntas de opción múltiple, divididas en seis campos: trabajo, ocio, relaciones personales, tratamiento, síntomas y sentimientos, que evaluan al individuo desde el punto de vista dermatológico y se pueden utilizar para medir o comparar la calidad de la vida entre diferentes enfermedades de la piel. La puntuación del instrumento varía de 0-30, cuando 0 se atribuye al mejor resultado y 30 al peor, siendo: sin deterioro de la calidad de vida (0-1), con deterioro leve (2-5), moderado (6-10), grave (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) o muy grave (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). El estudio de selección aportará información relevante sobre el estigma de la enfermedad de Hansen, atendiendo a los objetivos de la investigación.…”
Section: Materials Y Métodounclassified
See 1 more Smart Citation
“…El DLQI se compone de 10 preguntas de opción múltiple, divididas en seis campos: trabajo, ocio, relaciones personales, tratamiento, síntomas y sentimientos, que evaluan al individuo desde el punto de vista dermatológico y se pueden utilizar para medir o comparar la calidad de la vida entre diferentes enfermedades de la piel. La puntuación del instrumento varía de 0-30, cuando 0 se atribuye al mejor resultado y 30 al peor, siendo: sin deterioro de la calidad de vida (0-1), con deterioro leve (2-5), moderado (6-10), grave (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) o muy grave (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). El estudio de selección aportará información relevante sobre el estigma de la enfermedad de Hansen, atendiendo a los objetivos de la investigación.…”
Section: Materials Y Métodounclassified
“…Esta relación se verá influenciada por la capacidad que presentará el individuo frente a la queja, ya que en algunos pacientes la interferencia mínima proveniente de los síntomas puede causar efectos negativos, mientras otros individuos pueden reaccionar de manera diferente frente a la interferencia de estos síntoma(24) .Con respecto a la dimensión psicológica, la calidad de vida de las personas con la enfermedad de Hansen puede alcanzarse negativamente, ya que la sociedad configura un paradigma estético centrado en la belleza y la integridad física, que se puede cambiar debido a la enfermedad(13,14) . Además de esto, históricamente, como en muchos lugares, durante siglos, la enfermedad se consideró un castigo máximo proveniente de Dios, configurándose, sin embargo, en la modernidad, como una idea arcaica de la participación de la culpa y la infelicidad espiritual(25) .En general, es necesario resaltar el alto nivel de deterioro clínico observado entre los participantes de este estudio y con el consiguiente impacto de diversos niveles en su calidad de vida, con impedimentos por su funcionalidad, sociabilidad y autoestima. Tales resultados emergen reflexiones sobre las acciones que se están implementando en la atención a la salud de los pacientes en los diversos escenarios de asistencia, así como para buscar estrategias efectivas y eficientes que cambien esta realidad.…”
unclassified
“…Despite palaeopathological evidence for leprosy in the Pacific Islands prior to 1000 CE, some researchers have suggested that leprosy was absent in the Pacific Islands until the nineteenth century CE and was introduced as a result of European and Japanese imperialism or large-scale Chinese migration throughout the region [ 38 , 41 , 78 – 80 ]. However, if strains were introduced during the Japanese imperial occupations beginning in 1890, we would not expect to see such deep divergence between Japanese and Pacific Island strains.…”
Section: Discussionmentioning
confidence: 99%
“…They call the disease ma‘i pake , meaning ‘Chinese disease' and m‘ai ali‘i , meaning ‘chief's or royal disease' [ 36 , 37 ]. It has been argued that an uptick in leprosy cases occurred across the Pacific Islands during the 1800s [ 38 ]; this is probably a bias introduced by Western physicians diagnosing the disease and geopolitical pressure to isolate those affected on island colonies, for example Kalaupapa on Molokai or Makogai in Fiji [ 39 ]. Because the convincing skeletal evidence of leprosy on the Mariana Islands by 800 CE [ 26 , 40 ] is limited, it remains unresolved whether M. leprae was introduced during the initial island migrations or later during subsequent periods of colonialism and imperialism [ 41 ].…”
Section: Antiquity Of Mycobacterium Leprae Globallmentioning
confidence: 99%